Heavy Minerals: Methods & Case Histories - Andò, Sergio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The principal aim of this book is to provide a wide range of information and a useful reference for researchers interested to investigate heavy mineral assemblages in different geological settings and for a variety of purposes. The methodological developments achieved in recent years for the identification of heavy minerals in a wide grain-size range are illustrated. All factors that affect heavy mineral concentration and relative proportions, including hydraulic sorting, mechanical abrasion, chemical weathering, and post-depositional dissolution, and all factors able to introduce analytical, environmental, or diagenetic bias are thoroughly addressed. A proper integration of multiple techniques including bulk sediment, multi-mineral, and single-mineral methods are discussed by renowned authors in their invited contributions.